Excess-iron driven spin glass phase in Fe1 + yTe1 – xSex*The work at Beijing Normal University is supported by the National Natural Science Foundation of China (Grant Nos. 11734002 and 11922402, X.L.). Work at Rice is supported by the US Department of Energy (DOE), Basic Energy Sciences (BES), under Contract No. DE-SC0012311 (P.D.). A portion of this research used resources at the High Flux Isotope Reactor, a DOE Office of Science User Facility operated by the Oak Ridge National Laboratory. (August 2021) - Tian 田, Long 龙; Liu 刘, Panpan 盼盼; Hong 洪, Tao 涛; Seydel, Tilo; Lu 鲁, Xingye 兴业; Luo 罗, Huiqian 会仟; Li 李, Shiliang 世亮; Dai 戴, Pengcheng 鹏程
Abstract : The iron-chalcogenide superconductor FeTe1– x Se x displays a variety of exotic features distinct from iron pnictides. Although much effort has been devoted to understanding the interplay between magnetism and superconductivity near x = 0.5, the existence of a spin glass phase with short-range magnetic order in the doping range ( x ∼ 0.1–0.3) has rarely been studied. Here, we use DC/AC magnetization and (quasi) elastic neutron scattering to confirm the spin-glass nature of the short-range magnetic order in a Fe1.07 Te0.8 Se0.2 sample. The AC-frequency dependent spin-freezing temperature T f generates a frequency sensitivity Δ T f ( ω )/[ T f ( ω )Δlog10 ω ] ≈ 0.028 and the description of the critical slowing down with τ = τ 0 ( T f / T SG – 1) − z v gives T SG ≈ 22 K and zv ≈ 10, comparable to that of a classical spin-glass system. We have also extended the frequency-dependent T f to the smaller time scale using energy-resolution-dependent neutron diffraction measurements, in which the T N of the short-range magnetic order increases systematically with increasing energy resolution. By removing the excess iron through annealing in oxygen, the spin-freezing behavior disappears, and bulk superconductivity is realized. Thus, the excess Fe is the driving force for the formation of the spin-glass phase detrimental to bulk superconductivity.